PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS (Studi Empiris Pada Perusahaan Manufaktur Yang Bergerak disektor Aneka Industri Dan Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2016) - Neldawati Neldawati; Yusralaini Yusralaini; Riska Natariasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aimed to examine the influence of good corporate governance, profitability, and firm size on financial distress. The mechanism of good corporate governance in this study include the institutional ownership, number of boards of directors, and proportion of independent board of commissioners and audit committee. The population in this study is a Manufacturing Companies That Deal In The Various Sectors Of Industry And Consumer Goods Which Are Listen On The Indonesia Stock Exchange Period Of 2013 to 2016 which amounted to 75 companies. From the population obtained the total of samples of 32 companies which experiencing financial distress. Data obtained by using purposive sampling method and the financial distress measured by using Altman Z-Score (1968). This study uses multiple regression analysis. The results of this study that, (1) institutional ownership had no effect on financial distress, (2) the number of boards of directors had negative effect on financial distress, (3) proportion of independent board of commissioners had effect on financial distress, (4) audi committet had effect on financial distress, (5) profitability had effect on financial distress, and (6) firm size had no effect on financial distress.Keyword : institutional ownership, number of boards of directors, proportion of independent board of commissioners,audit commite, profitability, firm size, and financial distress